IDENTIFICATION OF ENDOPHYTIC BACTERIA FROM Curcuma zedoaria BASED ON PROTEIN PROFILE USING MALDI-TOF MASS SPECTROMETRY - Tri Ratna Sulistiyani; Puspita Lisdiyanti (SEAMEO BIOTROP, 2018)
Valid identification of microorganisms is vital information to establish culture collections. Currently, a molecular approach based on 16S rDNA is widely used for bacterial identification. However, this approach is time-consuming and expensive. Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) allows the identification of microorganisms directly from colonies, and it only takes a few minutes. The aim of this study was to identify endophytic bacteria associated with Curcuma zedoaria based on protein profiles using the MALDI-TOF MS system and to compare the results with 16S rDNA sequencing. Endophytic bacteria were isolated from parts of the medicinal plant C. zedoaria collected from Bogor, West Java, Indonesia. The identification of selected bacteria was performed using protein profiling via MALDI-TOF MS. A total of 66 endophytic bacteria from C. zedoaria were selected for identification. The results of MALDI-TOF MS analysis showed that eleven isolates (16.67%) were correctly identified at the species level, and twenty-three isolates (34.85%) matched the genus level of the molecular approach. These results demonstrate that the MALDI-TOF system is a suitable and feasible approach for bacterial identification, particularly for screening and grouping large numbers of isolates.